ИДИОМЫ КАК ОТРАЖЕНИЕ НАЦИОНАЛЬНОГО МЕНТАЛИТЕТА - СУТКЕВИЧ, АННА (Studia Rossica Posnaniensia, 2006)
In the article the importance of learning idioms as means of getting to know the national mentality is under consideration. The author underlines and analyses the factors influencing the origin of idioms and proves the necessity of studying them to completely understand the representatives of other cultures.